Fibroblasts activated by miRs-185-5p, miR-652-5p, and miR-1246 shape the tumor microenvironment in triple-negative breast cancer via PATZ1 downregulation - Giada De Luca; Gianluca Petrillo; Iolanda Scognamiglio; Katia Pane; Lorenza Cocca; Giuseppina Roscigno; Martina Mascolo; Claudia Pignataro; Sara Verde; Aurelia Fraticelli; Danilo Fiore; Alessandra Affinito; et al. (Cellular and Molecular Life Sciences)
Abstract The intricate interplay between epithelial and fibroblast cells within the tumor microenvironment plays a crucial role in driving triple-negative breast cancer progression. This crosstalk involves the exchange of various signaling molecules, including growth factors, cytokines, extracellular matrix components, and extracellular vesicles. Recently, we demonstrated that triple-negative breast cancer extracellular vesicles carry and release a specific combination of miRs, including miR-185-5p, miR-652-5p, and miR-1246 (from here on, referred as combo-miRs), into normal fibroblasts, effectively reprogramming them into cancer-associated fibroblasts. Here, we show that the conditioned medium from the fibroblasts activated by combo-miRs exerts a pro-tumorigenic effect on epithelial cells, enhancing the viability and migratory potential while driving increased invasiveness in patient-derived breast cancer organoids. A proteomic analysis of conditioned medium from combo-miRs activated fibroblasts revealed 76 significantly upregulated secreted proteins compared to control. Bioinformatic analysis identified the transcriptional factor PATZ1 as a potential regulator of the 12 most highly upregulated proteins. Consistently, in-silico predictions and in vitro experiments confirmed that PATZ1 is a direct target of miR-185-5p and miR-652-5p. The downregulation of PATZ1 by these miRNAs led to increased levels of the secreted proteins in the conditioned medium from combo-miRs activated fibroblasts. Furthermore, the conditioned medium from PATZ1-knockout mesenchymal embryonic fibroblasts and normal fibroblasts with silenced PATZ1 similarly enhanced the migratory potential of MCF10A cells, further supporting the critical role of PATZ1 in regulating tumor-promoting mechanisms. These findings provide valuable insights into the dynamics of the TME in TNBC, highlighting combo-miRs and PATZ1 as promising targets for future therapeutic interventions. Graphical Abstract